Interpersonal Communication Style Between Nurses and Patients At West Purwokerto Community Health Center - Madani, Aulia Arum; Turistiati, Ade Tuti; Dianingrum, Melia (LUGAS Jurnal Komunikasi, 2023)
This study aimed to analyze and discover the communication style of nurses and patients in health services at the West Purwokerto Health Center, as well as the barriers encountered in communication between nurses and patients and solutions to overcome communication barriers in health care. This study employs a qualitative descriptive approach, with data collected via observation, in-depth interviews, documentation, and literature reviews. The theory of social penetration was employed. According to the study's findings, the communication style between nurses and patients at the West Purwokerto Health Center was face-to-face with the stages of social penetration. The communication is started from ordinary to more intimate relations (self-disclosure). The communication style used by nurses and patients is patient-centered health care. Obstacles are encountered, such as the patient's character, which can be temperamental at times, and physical factors (patients with hearing loss), which can lead to misunderstandings. The nurse's solution is to re-explain in simpler language, provide patients with more understanding, and use non-verbal communication